Aquatic Insects of Palung Khola, Makwanpur District, Nepal - Yadav, R. P. (Our Nature, 2007)
The present study deals with aquatic insects of Palung Khola. The survey conducted from September, 2002 to March, 2004 enumerated 21 genera of aquatic insects belonging to19 families spread over 7 orders Key words: Aquatic insects, Palung Khola doi:10.3126/on.v4i1.510 Our Nature Vol. 4(1) 2006 pp104-106